Prognostic factors of readmission and mortality after first heart failure hospitalization: results from EPICAL2 cohort. (8th December 2022) - Varlot, Jeanne; Popovic, Batric; Soudant, Marc; Thilly, Nathalie; Agrinier, Nelly
Abstract: Aims: We aimed to identify prognostic individual factors in patients with first acute heart failure (HF) hospitalization, considering both death and readmission as part of the natural history of HF. Methods and results: We used data from the observational, prospective, multicentre EPICAL2 cohort study from which we selected incident cases of acute HF alive at discharge. We relied on an illness‐death model to identify prognostic factors on first readmission and on mortality before and after readmission. In 451 patients hospitalized for first acute HF, we observed within the year after discharge, 23 (5.1%) deaths before readmission and 270 (59.9%) first readmissions, of which 60 (22.2%) were followed by death of any cause. First, among patient characteristics, only Charlson index ≥ 8 was associated with first readmission [adjusted hazard ratio (aHR) = 1.6, 95% confidence interval (CI) (1.1–2.3), P = 0.011]. Second, Charlson index ≥ 8 [aHR = 4.2, 95% CI (1.2–14.8), P = 0.025], low blood pressure (BP) [aHR = 12.2, 95% CI (1.9–79.6), P = 0.009], high BP [aHR = 6.9, 95% CI (1.3–36.4), P = 0.023], and prescription of recommended dual or triple HF therapy at index discharge [aHR = 0.2, 95% CI (0.1–0.7), P = 0.014] were associated with mortality before any readmission. Third, Charlson index ≥ 8 [aHR = 2.4, 95% CI (1.1–5.6), P = 0.037] and the time to first readmission (per 30 days additional) [aHR = 1.2; 95% CI (1.1–1.4), P = 0.007] were associated with mortality after readmission. Conclusions: Regardless of the prognostic state considered, we showed that comorbidities are of critical prognostic value in a real‐world cohort of incident HF cases. This argues in favour of multidisciplinary care in HF.